Rancang Ulang Prototipe Pembangkit Listrik Tenaga Piko Hidro Portabel Tipe Cross Flow - Bella Maharani Marcellia Suseno (Politeknik Negeri Jakarta, 2022)
Electricity is one of the most important needs in everyday life. The need for lighting for study or research purposes in a field that has not been reached by a power source makes a portable Pico Hydro Power Plant (PLTPH) a solution to obtaining electricity supply by utilizing a water source with a fairly small discharge and head. The steps that have been taken in the design of the portable PLTPH include a study of the PLTPH that was once designed by Dzulfikri (2021), reverse engineering of the portable PLTPH such as inlet and outlet, the shape of the turbine housing, supports, turbine runners, testing installations, and nozzle cross-sectional area. Next, prepare the test installation. The testing process was carried out and continued with the discussion of the test results. The dimensions of the tool are 266.63 mm long, 190 mm wide, and 226.88 mm high, which were made using a 3D Printing machine using PLA plastic material. The results of the reverse engineering test results have a rotational speed of 794 rpm, a discharge of 3,867 l/s, and a head of 2 m, resulting in a mechanical power of 20.13 W and an efficiency of 26.0%. These results produce greater mechanical power and efficiency than the existing equipment (mechanical power of 11.7 W and efficiency of 23%). Keywords: Pico Hydro, Portable, Reverse Engineering, Cross Flow